A genome-wide association study for varicose veins. (May 2022) - Lee, Meng-Lin; Liang, Chao; Chuang, Cheng-Hsun; Lee, Pei-Shyuan; Chen, Thay-Hsiung; Sun, Shen; Liao, Kuang-Wen; Huang, Hsien-Da
Background: The aim was to compare the genetic information of varicose vein patients with that of a healthy population attempting to identify certain significant genetic associations. Method: Patients' clinical characteristics and demographics were collected, and their genetic samples were examined. The results were compared to the genetic information of one thousand sex-matched healthy controls from Taiwan Biobank database. The Clinical-Etiology-Anatomy-Pathophysiology classification was applied for further subgroup analysis. Results: After comparison of genetic information of ninety-six patients to that of healthy controls, two significant single nucleotide polymorphisms (SNPs) were identified. One was in DPYSL2 gene, and the other was in VSTM2L gene. A further comparison between C2-3 patient subgroup and C4-6 subgroup identified another four significant SNPs, which were located in ZNF664-FAM101A, PHF2, ACOT11, and TOM1L1 genes. Conclusion: Our preliminary result identified six significant SNPs located in six different genes. All of them and their genetic products may warrant further investigations.